Research of Mining Area Ecological Compensation From the Perspective of Knowledge Innovation - Xing, Qinfeng; Gang, He; Yao, Wanyan (Frontiers in Environmental Science, 2022)
Ecological compensation has been the favorite subject of ecological depletion caused in mining areas with the aim of sustainable development. So, an analytical model is presented to assess the knowledge innovation of ecological compensation. Later, the methods of factor analysis, resistance diagnosis, and multiple regressions are integrated to evaluate its satisfaction in the Huainan mining area. The study found that (1) the influence of factors related to work mechanism is identical, while the influence of factors related to strategic planning and action skills is heterogenous; and (2) in terms of the relative importance of the three dimensions of work mechanism (0.479), strategic planning (0.467), and action skills (0.351), their influence decreases in order. The results can provide reference materials for the effective governance of ecological compensation and its scientific management of ecological safety in the mining area. So, the findings can help for better improvement of ecological compensation, and then the following strategies are proposed to improve its knowledge innovation: First, the harmonious development of individual behavior and overall interests needs to be realized; Second, the coordinated development of top-level design and adherence to faith needs to be optimized; Third, the interactive development guided by competence and mass entrepreneurship and innovation needs to be achieved.